Sex differences in the contributions of spinal atypical PKCs and downstream targets to the maintenance of nociceptive sensitization. (May 2019) - George, Nicole C; Laferrière, André; Coderre, Terence J
Background: Chronic pain has been shown to depend on nociceptive sensitization in the spinal cord, and while multiple mechanisms involved in the initiation of plastic changes have been established, the molecular targets which maintain spinal nociceptive sensitization are still largely unknown. Building upon the established neurobiology underlying the maintenance of long-term potentiation in the hippocampus, this present study investigated the contributions of spinal atypical protein kinase C (PKC) isoforms PKCι/λ and PKMζ and their downstream targets (p62/GluA1 and NSF/GluA2 interactions, respectively) to the maintenance of spinal nociceptive sensitization in male and female rats. Results: Pharmacological inhibition of atypical PKCs by ZIP reversed established allodynia produced by repeated intramuscular acidic saline injections in male animals only, replicating previously demonstrated sex differences. Inhibition of both PKCι/λ and downstream substrates p62/GluA1 resulted in male-specific reversals of intramuscular acidic saline-induced allodynia, while female animals continued to display allodynia. Inhibition of NSF/GluA2, the downstream target to PKMζ, reversed allodynia induced by intramuscular acidic saline in both sexes. Neither PKCι/λ, p62/GluA1 or NSF/GluA2 inhibition had any effect on formalin response for either sex. Conclusion: This study provides novel behavioural evidence for the male-specific role of PKCι/λ and downstream target p62/GluA1, highlighting the potential influence of ongoing afferent input. The sexually divergent pathways underlying persistent pain are shown here to converge at the interaction between NSF and the GluA2 subunit of the AMPA receptor. Although this interaction is thought to be downstream of PKMζ in males, these findings and previous work suggest that females may rely on a factor independent of atypical PKCs for the maintenance of spinal nociceptive sensitization.